Analisis Kemampuan Literasi Matematis Siswa Ditinjau dari Karakter Belajar Aljabar di Sekolah Dasar - Wirda Indri Khairizka; Amiruddin Amiruddin; Vira Dwi Nanda; Tasya Fatihah; Siti Aminah (Departement of Mathematics Education, 2023)
This study aims to describe the ability of elementary school students' mathematical literacy in algebraic material in terms of students' learning characteristics. This research method is a Qualitative Method. The subjects of this study were students of class IV A at SD Nusantara Lubuk Pakam. The data collection instrument used a learning independence questionnaire, tests of mathematical literacy abilities, and questions and answers. Indicators in this study Indicators selected from knowledge, attitudes and practices as measured by surveys that influence internal factors, namely factors from the students themselves. The research analysis uses the Miles and Huberman models, namely, data reduction, data presentation, and drawing conclusions. The results of the study show that students' mathematical literacy abilities in terms of the character of independent learning, have an average in the moderate category. Some students are less able to understand, accept, or digest subject matter regarding mathematical literacy.